Effect of soil texture on Nacl dispersivity in soil and simulating by Hydrus 2D model - Masoomeh Farasati (علوم و مهندسی آبیاری, 2015)
Evaluation of dispersivity in different soil textures can be used in solving problems related to pollutants migration of groundwater. Numerical models are frequently used for simulation of water movement in soils. In the present study, the dependence of dispersivity on the soil texture has been investigated. The textures of soils consisted of medium sand particles and medium sand particles with 25, 50 and 75 percent (by weight) of coarse sand and coarse designated by T1, T2, T3, T4 and T5 with 40 cm height of soil column respectively. For calculation of dispersivity Brigham model and for simulation of salinity movement HYDRUS software used. Results of the study indicated that the dispersivity of sandy soil was dependent on the particle size and mixture of textures. And with increase of coarse soil, dispersivity increased.